Minat Mahasiswa ASM Santa Maria Semarang Angkatan 2019/2020, 2020/2021, 2021/2022 untuk Menggunakan Uang Elektronik (UE) dalam Bertransaksi - Bambang Kristianto Wibowo; Naniek Risnawati (Sekolah Tinggi Ilmu Ekonomi Semarang, 2023)
One of the impacts of advances in information and communication technology in the economic sector is that it makes it easier for people to transact using electronic money which is faster, safer, and healthier. Electronic money is legally regulated in BI Decree No. 20/6/PBI/2018 and Law no. 19 of 2016 concerning Information and Electronic Transactions using computers, computer networks or other electronic media. In the daily life of ASM Santa Maria Semarang students for the academic year 2019/2020 to.d. 2021/2022 most (52%) have used the electronic money. 48% have not used gadgets in transactions because not all students have NFC (Near Field Communication) on their gadgets. This research method uses a qualitative exposure approach through a numbered questionnaire.The results of this study are that ASM Santa Maria Semarang students for the academic year 2019/2020 – 2021/2022 really understand the types of electronic money used. The media used to support the use of electronic money are smartphone-type mobile phones and ATM machines. Students use electronic money because electronic money has many benefit. The inhibiting factor forstudents in using electronic money is that not all students have NFC (Near Field Communication) on their smartphones, and not all students have smartphones.